A reactive collision avoidance approach for mobile robot in dynamic environments - Tang, Sai Hong; Ang, Chun Kit; Nakhaeinia, Danial; Karasfi, Babak; Motlagh, Omid Reza Esmaeili (Engineering and Technology Publishing, 2013)
This paper describes a novel reactive obstacle avoidance approach for mobile robot navigation in unknown and dynamic environment. This approach is developed based on the “situated-activity paradigm” and a “divide and conquer” strategy which steers the robot to move among unknown obstacles and towards a target without collision. The proposed approach entitled the Virtual Semi-Circles(VSC). The VSC approach lies in integration of 4 modules: division, evaluation, decision and motion generation. The VSC proposes a comprehensive obstacle avoidance approach for robust and reliable mobile robot navigation in cluttered, dense and complex unknown environments. The simulation result shows the feasibility and effectiveness of the proposed approach.